Regulation of rat urinary and renal kallikrein and prekallikrein by corticosteroids. - Noda, Y (1983)
Rats were adrenalectomized and injected for 7 days with dexamethasone (DEX) or deoxycorticosterone. Kallikrein and prekallikrein were assayed in urine and in a basolateral membrane-enriched fraction. The activities of renin and phospholipase A2 were also determined in the fraction. Adrenalectomy significantly decreased active kallikrein in urine. Administration of deoxycorticosterone raised the level of active kallikrein in urine without affecting the concentration of prekallikrein. Rats treated with DEX only had high Na+ and low active kallikrein excretion. The total kallikrein level (active kallikrein together with prekallikrein), however, returned to normal because DEX elevated the prekallikrein level. DEX also increased the prekallikrein concentration in the membrane-enriched fraction. Renin activity in the membrane-enriched fraction was enhanced by adrenalectomy but suppressed by either corticosteroid. The changes in the concentration of plasma renin were qualitatively similar but quantitatively different. The activity of phospholipase A2 in the membrane-enriched fraction was enhanced only by deoxycorticosterone. Thus, both gluco- and mineralocorticoids increased kallikrein excretion in the adrenalectomized animals, but DEX was apparently effective at a lower dose than deoxycorticosterone. DEX increases the prekallikrein concentration in urine and on the basal membrane of distal tubular cells and, in addition, may prevent its conversion by releasing an inhibitor of a prekallikrein activator.